Inhibitory activity of metal-curcumin complexes on quorum sensing related virulence factors of Pseudomonas aeruginosa PAO1 - Mina Gholami (AMB Express, 2020)
Abstract The use of metal complexes to reduce or inhibit virulence factors of Pseudomonas aeruginosa is a promising strategy for the management and control of infections caused by this multidrug-resistant pathogen. The present study aimed to investigate the anti-quorum sensing activity of sub-minimum inhibitory concentrations (sub-MIC) of copper(II) sulfate pentahydrate-curcumin complex (Cu-CUR), iron(III) nitrate nonahydrate -curcumin complex (Fe-CUR), zinc(II) chloride-curcumin complex (Zn-CUR) and free curcumin (free-CUR) against P. aeruginosa PAO1. Metal-CUR complexes were synthesized and characterized by spectroscopic methods. The effect of sub-MIC (1/4 and 1/16 MIC) concentrations of metal-CUR complexes and free-CUR on cell growth, biofilm formation, motility, alginate and pyocyanin production, H2O2 susceptibility and expression of lasI and lasR genes in PAO1 was determined. MIC of metal-CUR complexes and free-CUR was determined as 62.5 and 125 µg/ml, respectively. Metal-CUR complexes at concentration of 62.5 µg/ml significantly reduced the cell growth to 1.5%–3.3%. Although we did not measure the anti-QS activity of metal-CUR complexes directly against PAO1, they indicated anti-QS activity in C. violaceum CV026. Copper-CUR complex at the concentration of 1/4 MIC showed the greatest inhibitory effect on swarming and twitching motilities, biofilm formation, alginate and pyocyanin production, sensitivity to H2O2 and reduction in the expression levels of lasI and lasR genes (P < 0.001). Considering the biological effects of Cu-CUR complex and its inhibitory activity on virulence factors, it may be used as an effective compound for treatment and control of infections caused by P. aeruginosa.